2004
DOI: 10.3386/w10980
|View full text |Cite
|
Sign up to set email alerts
|

Why Should We Care About Child Labor? The Education, Labor Market, and Health Consequences of Child Labor

Abstract: Although there is an extensive literature on the determinants of child labor and many initiatives aimed at combating it, there is limited evidence on the consequences of child labor on socioeconomic outcomes such as education, wages, and health. We evaluate the causal effect of child labor participation on these outcomes using panel data from Vietnam and an instrumental variables strategy. Five years subsequent to the child labor experience, we find significant negative impacts on school participation and educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 0 publications
8
139
0
11
Order By: Relevance
“…On average, children and adolescents who work are two years behind their standard school year and only one of every four children who work concludes their basic education. 31,32 This scenario is worrisome given that participation in education contributes to achieving social equity as well as constituting an opportunity for social integration and, evidently, acquiring skills and knowledge. 33,34 Our study also found that Mexican children and adolescents 5-17 years of age who do child labor, do principally dangerous work (8.5%) or work outside the home, with few doing housework or chores above the level indicated for their age.…”
Section: Discussionmentioning
confidence: 99%
“…On average, children and adolescents who work are two years behind their standard school year and only one of every four children who work concludes their basic education. 31,32 This scenario is worrisome given that participation in education contributes to achieving social equity as well as constituting an opportunity for social integration and, evidently, acquiring skills and knowledge. 33,34 Our study also found that Mexican children and adolescents 5-17 years of age who do child labor, do principally dangerous work (8.5%) or work outside the home, with few doing housework or chores above the level indicated for their age.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that child labor can increase incidence of illness up to five years after starting to work. Using a different estimation strategy, Beegle et al (2004) did not find significant adverse health consequences of child labor.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Most studies in this literature seek to estimate the causal effect of one of these activitiesthat is child labor or schooling-on the other. They do so either by exploiting shocks to the returns to labor-for example the profitability of farm labor or local labor market conditions (Beegle Dehejia, and Gatti 2009)-or to the price or benefits of school (Ravallion and Wodon 2000). We pose a related question, which has received less attention than these others: How do productivity shocks that affect the child change the allocation of time across both schooling and labor?…”
Section: Introductionmentioning
confidence: 99%
“…Further, a growing number of studies have demonstrated that child labor matters. For example, it has been shown that child labor reduces schooling (Kruger 2007) and has effects on health and wages which can persist into adulthood (Beegle, Dehejia, and Gatti 2009). 1 Most studies in this literature seek to estimate the causal effect of one of these activitiesthat is child labor or schooling-on the other.…”
Section: Introductionmentioning
confidence: 99%